Incidence of Several Forms of Tuberculosis (TB) and Their Bacillus Calamette Guerin (BCG) Vaccination Status among Children - Omair Mazhar, Sher Alam Khan, Muhammad Arsalan Qaisar, Zafar Iqbal Bhatti, Mahwish Akhtar Qureshi, Ibrahim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of the study was to govern the incidence of various forms of tuberculosis and the status of BCG vaccination in children. Study design: A Cross-sectional study. Place and Duration of the Study: In the Pediatrics department of Jinnah hospital, Lahore for one-year duration from January 2021 to December 2021. Methods: A total of 200 patients with various forms of tuberculosis were recruited who met the inclusion and exclusion criteria. A demographic profile including age, gender and hospital registration numbers is recorded. Informed oral consent was obtained from the parents of each child. BCG scar present or absent. Form of tuberculosis, pulmonary tuberculosis (fever> 14 days, ESR> 50, sputum positive for AFB, x-ray results), tuberculous meningitis (fever with focal neurological symptoms lasting longer than 14 days, CT results according to inclusion criteria, CSF pleocytosis), tuberculous lymphadenitis (detection of tuberculosis by histopathology on excisional lymph node biopsy), abdominal tuberculosis (fever longer than 14 days, previous weight loss and anorexia, mesenteric lymphadenitis, biopsy of the lesion suggestive of tuberculosis), description and labelling of the vaccinated and unvaccinated patient with the presence or absence of BCG scar. Results: During this period, 200 patients who met the exclusion and inclusion criteria were selected in the study. Of the 200 patients included, 110 (55%) were males and 90 (45%) were females (Table 1), their age varies from 1 to 14 years, with 7.22 ± 3.78 years of an average age. Out of 200 enrolled patients, the four most common types of tuberculosis were examined. Out of 200 cases, 95 (47.5%) were pulmonary tuberculosis, 50 (25%) tuberculous meningitis, 35 (17.5%) tuberculous lymphadenitis, and 25 (12.5%) abdominal tuberculosis. Of the 200 patients enrolled, 85 (42.5%) were vaccinated (with BCG scarring) and 115 (57.5%) were unvaccinated. Keywords: Tuberculosis, BCG, Pulmonary tuberculosis